Nilai Pendidikan Islam Dalam Kisah Nabi Ibrahim AS Kajian Tafsir QS. Al-Mumtahanah Ayat 4 - Saefuddin, Ahfadl; Darodjat, Darodjat; Makhful, Makhful (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
This research is motivated by the need to understand and analyze the values ​​of Islamic education in the context of the story of the Prophet Ibrahim. The method used in this research is qualitative descriptive analysis. It is hoped that this research can make a positive contribution to the development of Islamic education in Indonesia, especially in terms of instilling Islamic educational values ​​that are in accordance with the teachings of the Islamic religion and the socio-cultural context of Indonesian society. When children have established faith in their childhood and have the principles of monotheism embedded in their brains and minds, then the destroyers will not be able to influence them. The advocates of falsehood will also not be able to influence his mature brain. Man will not be able to tear apart the person he has given. Because his personality has been filled with strong faith, deep conviction, and perfect qana'ah (receiving God's gift).